2021
DOI: 10.3389/fmicb.2021.710940
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-Associated Microbial Profile Is Altered in Small Intestinal Bacterial Overgrowth

Abstract: The overall gut microbial profile of patients with small intestinal bacterial overgrowth (SIBO) has not been thoroughly investigated. We investigated the microbial communities of mucosal specimens from the duodenum, ileum, sigmoid colon, and feces of patients with and without SIBO, as diagnosed by lactulose breath testing. The bacteria present in the mucosal and fecal samples were identified using 16S rRNA gene sequencing. Further analysis was performed using the linear discriminant analysis (LDA) effect size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
0
14
0
1
Order By: Relevance
“…However, the efforts in characterizing the small intestinal ecology in SIBO patients may result in diverging results due to the difference in sampling locations across different study cohorts (Leite et al 2020a , Li et al 2021 ) (Table 7 ). Additionally, inconsistencies among SIBO studies might also be related to the type of SIBO, often not indicated.…”
Section: Disruption Of Small Intestinal Homeostasis In Nutrient Balancementioning
confidence: 99%
“…However, the efforts in characterizing the small intestinal ecology in SIBO patients may result in diverging results due to the difference in sampling locations across different study cohorts (Leite et al 2020a , Li et al 2021 ) (Table 7 ). Additionally, inconsistencies among SIBO studies might also be related to the type of SIBO, often not indicated.…”
Section: Disruption Of Small Intestinal Homeostasis In Nutrient Balancementioning
confidence: 99%
“…According to a recent study, mucosal microbial compositions were significantly different, and microbial richness values were dramatically lower in the ileac of SIBO-positive participants than in those negative for SIBO. This suggests that SIBO may be an indicator of intestinal flora dysbiosis [27]. Therefore, we explored the occurrence of such dysbiosis in patients with AIS by assessing SIBO.…”
Section: Discussionmentioning
confidence: 99%
“…After bowel preparation with oral polyglycol powder, colonoscopy was performed for each subject to take a biopsy of the terminal ileum, 5–10 cm from the ileocecal valve as described in previous studies [ 9 , 22 ]. The biopsy was taken during insertion, not exit, of the colonoscopy to minimize contamination of the proximal intestine by microbiota.…”
Section: Methodsmentioning
confidence: 99%
“…As described in previous studies [ 9 ], the V3–V4 hypervariable region of the 16S rRNA bacterial gene was amplified by PCR using Primers 338F (5′-ACTCCTACGGGAGGCAGCAG-3′) and 806R (5′-GGACTACHVGGGTWTCTAAT-3′). A total of three amplification replicates with a volume of 20 μl were obtained for each sample, and all PCR products from these three replicates were aggregated, as well as purified and quantified using the AxyPrep DNA Gel Extraction Kit (Axygen, USA) and a Quantus™ Fluorometer (Promega, USA), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation